2015
DOI: 10.3354/meps11113
|View full text |Cite
|
Sign up to set email alerts
|

Tumbling under the surf: wave-modulated settlement of intertidal mussels and the continuous settlement-relocation model

Abstract: For many mussel species, the model of planktonic development followed by metamorphosis and settlement in the benthic habitat is complicated by the existence of planktonic post-metamorphic stages and/or pediveliger benthic stages that can relocate after initial settlement. This has led to the long-standing hypothesis of 'primary' settlement from the plankton onto intertidal algal substrate followed by 'secondary' relocation to mussel beds. Here, we investigate settlement of the intertidal mussels Perumytilus pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 70 publications
0
23
0
1
Order By: Relevance
“…Larvae that sink or swim down may enter near-bed streaming and thus be transported shoreward. Our data, along with that of Navarrete et al (2015) and Morgan et al (2009) suggest that competent larvae can enter the surf zone via near-bed streaming, and given the universality of the associated physics, that this transport mechanism could be exploited by larvae on all shores. …”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Larvae that sink or swim down may enter near-bed streaming and thus be transported shoreward. Our data, along with that of Navarrete et al (2015) and Morgan et al (2009) suggest that competent larvae can enter the surf zone via near-bed streaming, and given the universality of the associated physics, that this transport mechanism could be exploited by larvae on all shores. …”
Section: Discussionmentioning
confidence: 56%
“…This hypothesized mechanism of surf zone entrainment of detritus works when waves are small enough that detritus and zooplankters can settle to the seabed and remain there long enough for streaming to transport them into the surf zone. Navarrete et al (2015) presented data suggesting that 2 species of intertidal mussels in Chile use streaming to cross the inner shelf and surf zone to settle in the intertidal. Larvae of these species settle and metamorphose offshore, but likely close to shore.…”
Section: Discussionmentioning
confidence: 99%
“…Benthic streaming may increase entry of zooplankton into the surf zone at the RSZ, where only demersal taxa, including harpacticoid copepods, juvenile parasitic isopods seeking host shrimp and cyprids were more abundant inside than outside the surf zone. Streaming is suppressed by breaking waves at the seaward edge of the surf zone, but zooplankton, detritus and sediments near the bottom enter the surf zone by entrainment into breaking waves [25][26][27]. Although some species of cyprids have been reported to be more abundant near the sea surface [28][29][30], we previously demonstrated that cyprids of all species recruited almost entirely to the bottom of moorings just outside the surf zone over 5 years on this coast [31].…”
Section: Discussionmentioning
confidence: 87%
“…Plankton near the surface may be transported into the surf zone via the sea breeze during the daytime (Jacinto and Cruz ) or via Stokes drift in large shoaling waves that are refracted toward shore (Morgan et al a ; McPhee‐Shaw et al ). Plankton near the bottom may be transported together with sediment through the surf zone by benthic streaming (Lentz et al ; Navarrete et al ; Shanks et al ). Benthic streaming may deliver heavy zooplankters that passively sink to the bottom following mixing by large waves (Navarrete et al ) or swim to the bottom in response to turbulence (Fuchs and DiBacco ; Roy et al ; Fuchs et al ).…”
mentioning
confidence: 99%